Techniques in protein chemistry. - Marshak, Daniel R. (Techniques in Protein Chemistry., 1996)
Techniques in Protein Chemistry VII, a valuable bench-top reference tool for protein chemists, features the most up-to-date advances in protein methodologies. Key Features* Protein sequencing and amino acid analysis* Mass spectral analysis of peptides and proteins* Posttranslational processing* High-sensitivity protein and peptide separations* Protein folding and NMR* Functional domain analysis* Protein design and engineering.